2017
DOI: 10.1007/978-1-4939-7030-8_1
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Introduction into the Renin-Angiotensin-Aldosterone System: New and Old Techniques

Abstract: The renin-angiotensin-aldosterone system (RAAS) is a complex system of enzymes, receptors, and peptides that help to control blood pressure and fluid homeostasis. Techniques in studying the RAAS can be difficult due to such factors as peptide/enzyme stability and receptor localization. This paper gives a brief account of the different components of the RAAS and current methods in measuring each component. There is also a discussion of different methods in measuring stem and immune cells by flow cytometry, hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 163 publications
0
5
0
Order By: Relevance
“…It is a part of the renin-angiotensin-aldosterone system (RAAS) that modulates the release of angiotensin. 99 The direct effects of angiotensin Author Manuscript blockade on the structural and electrical properties of the atria, as well as the indirect influence of improved control of heart failure and hypertension, are considered to mediate a potential risk reduction for the development of poAF. 100 Randomized, controlled trials have shown that angiotensin II-receptor blockers (ARBs) reduces poAF (RR = 0.78; 95% CI: 0.66 -0.92), with similar but non-significant results for ACE-inhibitors (RR = 0.79, 95% CI: 0.62 -1:00).…”
Section: Renin-angiotensin Inhibition (Ace-inhibitors Angiotensin II Receptor Blockers and Aldosterone) (Eg Enalapril Ramipril Perindoprimentioning
confidence: 99%
“…It is a part of the renin-angiotensin-aldosterone system (RAAS) that modulates the release of angiotensin. 99 The direct effects of angiotensin Author Manuscript blockade on the structural and electrical properties of the atria, as well as the indirect influence of improved control of heart failure and hypertension, are considered to mediate a potential risk reduction for the development of poAF. 100 Randomized, controlled trials have shown that angiotensin II-receptor blockers (ARBs) reduces poAF (RR = 0.78; 95% CI: 0.66 -0.92), with similar but non-significant results for ACE-inhibitors (RR = 0.79, 95% CI: 0.62 -1:00).…”
Section: Renin-angiotensin Inhibition (Ace-inhibitors Angiotensin II Receptor Blockers and Aldosterone) (Eg Enalapril Ramipril Perindoprimentioning
confidence: 99%
“…Renin-angiotensin aldosterone system (RAAS) [48,49] is a complex system comprising many peptides, receptors, and enzymes [50]. RAAS is considered a key element in maintaining the hemostatic of the body fluid, electrolytes, and arterial blood pressure [51].…”
Section: Renin Angiotensin Aldosterone Systemmentioning
confidence: 99%
“…Renin-angiotensin aldosterone system (RAAS) [48,49] is a complex system comprising many peptides, receptors, and enzymes [50]. RAAS is considered a key element in maintaining the hemostatic of the body fluid, electrolytes, and arterial blood pressure [51].…”
Section: Renin Angiotensin Aldosterone Systemmentioning
confidence: 99%